2022
DOI: 10.1097/jw9.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the management of treatment-resistant pediatric atopic dermatitis

Abstract: Atopic dermatitis (AD) is a prevalent protracted inflammatory skin condition that affects approximately 12% of children globally. Topical remedies, such as pharmacologic and nonpharmacologic management, and off-label systemic medicines, have traditionally been used to treat pediatric AD patients. To minimize comorbidities, sleep disturbances, pruritus, and signs of inflammation and improve the patient’s quality of life, it is vital to optimize severe AD management in pediatric patients. Treatment resistance ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Follow-up data also revealed a long period of disease remission even after completion of therapy [20]. Adverse effects of phototherapy may include skin burning, transient erythema, pruritus, herpes simplex virus reactivation, and a potentially increased risk for skin cancer, particularly with psoralen (PUVA) [21,22]. These effects warrant attention in the pediatric population, given their longer life expectancy and potential risk for long-term damage [22].…”
Section: Phototherapymentioning
confidence: 99%
See 3 more Smart Citations
“…Follow-up data also revealed a long period of disease remission even after completion of therapy [20]. Adverse effects of phototherapy may include skin burning, transient erythema, pruritus, herpes simplex virus reactivation, and a potentially increased risk for skin cancer, particularly with psoralen (PUVA) [21,22]. These effects warrant attention in the pediatric population, given their longer life expectancy and potential risk for long-term damage [22].…”
Section: Phototherapymentioning
confidence: 99%
“…These effects warrant attention in the pediatric population, given their longer life expectancy and potential risk for long-term damage [22]. Combined with the challenge of scheduling phototherapy on a weekly basis and ensuring proper protection throughout the treatment course, many authors recommend against use of phototherapy in infants and young children [19,21]. Though long-term data on the safety of phototherapy are still lacking, numerous studies currently support the safety of administering NBUVB to children [21,22].…”
Section: Phototherapymentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that children with AD are more likely to have allergies, asthma, and mental health problems ( 5 ). Infants and children with AD are often treated with topical corticosteroids, antihistamines, and even antibiotics ( 6 ). However, these drugs have some side effects, and AD symptoms may recur quickly after the treatment is stopped.…”
Section: Introductionmentioning
confidence: 99%